Kinesiology taping with exercise does not provide additional improvement in round shoulder subjects with impingement syndrome: A single-blinded randomized controlled trial. (November 2019) - Kang, Fu-Jie; Chiu, Yuan-Chun; Wu, Shu-Chi; Wang, Tyng-Guey; Yang, Jing-lan; Lin, Jiu-Jenq
Abstract: Objective: Round shoulder posture (RSP) may exaggerate symptoms of subacromial impingement. The effects of kinesiology taping with exercise on posture, pain, and functional performance were investigated in subjects with impingement and RSP. Design: This study was a single-blinded randomized controlled trial. Setting: An outpatient rehabilitation clinic in a university hospital. Participants: Thirty-four subjects with subacromial impingement and RSP. Interventions: Kinesiology taping with and without tension was applied 2 times per week for 4 weeks. Both groups also performed strengthening and stretching exercises 3 times per week for 4 weeks. Main outcome measurements: The pain level, shoulder angle and self-reported score were evaluated at pre-intervention, 2-week post-intervention and 4-week post-intervention time points. Results: Functional performance improved after intervention in both groups (p = 0.027). A greater decrease in pain level was related to better functional performance of the shoulder in both groups ( r = −0.760 and −0.674; p < 0.010). Moderate correlations were found for posture and functional performance of the shoulder in the intervention group (0.48). Conclusion: Four weeks of strengthening and stretching exercises with or without kinesiology taping improved functional performance in subjects with impingement and RSP. Improvement in clinical symptoms was related to better performance of posture. Highlights: Four weeks of strengthening and stretching exercises improves functional performance in subjects with impingement and RSP. Kinesiology taping did not demonstrate an additional effect on RSP in our sample. For subjects with SIS and RSP, improvement in clinical symptoms like pain and functional activity are related to better performance of posture.